Prognostic impact of preoperative inflammatory biomarkers in acute limb ischemia patients: a systematic review - Coelho,Nuno Henriques (2020)
Abstract Introduction: In many areas of Medicine, biomarkers have been proving their value in disease management. The inclusion of inflammatory biomarkers in acute limb ischemia (ALI) decision-making remains debatable due to the scarce literature evidence. Nevertheless, much attention has been held towards the prognostic value of these simple, readily available and low-cost biomarkers might have. Therefore, this review aimed to identify studies that support the utility of preoperative inflammatory markers, such as the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR), for predicting ALI outcome. Methods: A comprehensive systematic search was applied to Medline database to identify all the cohort studies that specifically investigated and compared the outcomes of ALI patients in relation to their preoperative inflammatory biomarkers. Results: Four cohort studies were included in the review: two published citations, one research letter and one unpublished paper from the same authors of this review. In all studies, the primary outcomes were amputation and/or survival. All studies reported that higher NLR values were independently associated with adverse outcomes after treatment. One study stated that NLR e 5.2 was found to have an 83% sensitivity and 63% specificity for predicting amputation within 30 days (Area Under Curve (AUC) 0.8) while other found that NLR e 5.4 demonstrated to have a 90.5% sensitivity and 73.6% specificity for predicting 30-day amputation or death (AUC 0.86). Higher preoperative RDW, MPV, PLR and C-reactive protein were also reported as predictors of amputation in acute arterial thromboembolism patients in another study. Conclusion: This review demonstrates that although limited literature exists, inflammatory biomarkers like NLR and PLR appear to have a role in ALI preoperative risk stratification. Definition of levels and trends of inflammatory biomarkers and their relationship with treatment outcome could be established through multicentric studies, influencing timing and intervention selection and leading to potential improvements in ALI morbimortality.